PENGARUH MOTIVASI KERJA DAN GAYA KEPEMIMPINAN TERHADAP KINERJA PENGHULU - Wiharso, SL. Triyaningsih & (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2007)
ABSTRACT Target of this research to study and analyze supervision influence, job motivation and leadership style to Moslem Chief performance in Religion Departmental office Sub-Province Karanganyar by partial and also together. Intake of samples with census to 25 chieftain. Its result indicate that by partial, supervision have an effect on significant to Moslem Chief performance, but job motivation and leadership style do not have an effect on significant. For that require to be improved by motivation pushing Moslem Chief performance and apply democratic leadership style, receptive and transparent of suggestion and also criticism from its staff. Keywords: supervision, job motivation, leadership style, Moslem Chief performance